2022
DOI: 10.3390/molecules27134156
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Cyclization of 5H-Chromeno[2,3-b]pyridines to Benzo[b]chromeno[4,3,2-de][1,6]naphthyridines, Their NMR Study and Computer Evaluation as Material for LED

Abstract: Oxidative cyclization is one of the most significant reactions in organic synthesis. Naphthyridine derivatives are often used as luminescence materials in molecular recognition because of their rigid planar structure and as new drugs. Organic light-emitting diodes (OLEDs) have rapidly grown as one of the leading technologies for full-color display panels and eco-friendly lighting sources. In this work, we propose the synthesis of previously unknown benzo[b]chromeno[4,3,2-de][1,6]naphthyridines via intermolecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Recently, Elinson et al reported the synthesis of benzo[ b ]chromeno[4,3,2-de][1,6]naphthyridines via an intermolecular oxidative cyclization of 5-(2-hydroxy-6-oxocyclohexyl)-5H-chromeno[2,3- b ]pyridines in formic acid. 15…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Elinson et al reported the synthesis of benzo[ b ]chromeno[4,3,2-de][1,6]naphthyridines via an intermolecular oxidative cyclization of 5-(2-hydroxy-6-oxocyclohexyl)-5H-chromeno[2,3- b ]pyridines in formic acid. 15…”
Section: Introductionmentioning
confidence: 99%
“…14 Recently, Elinson et al reported the synthesis of benzo[b] chromeno [4,3,2-de][1,6]naphthyridines via an intermolecular oxidative cyclization of 5-(2-hydroxy-6-oxocyclohexyl)-5H-chromeno [2,3-b] pyridines in formic acid. 15 In this line of research and in continuation of our research on the synthesis of novel heterocycles, 16 herein, we report an efficient method for the synthesis of chromeno [1,6]naphthyridine derivatives via a one-pot, three-component condensation reaction between salicylaldehyde derivatives, malononitrile dimer, and active methylene group compounds (5-amino-3-(cyanomethyl)-1H-pyrazole-4carbonitrile/5-amino-3-(cyanomethyl)isoxazole-4 carbonitrile/2-(cyanomethyl) pyrazolo [1,5-a]pyrimidine-3-carbonitrile derivatives/ malononitrile dimer/alkyl malonates) in polyethylene glycol-400 (PEG-400) at 80 1C (Scheme 1). This new nominally catalyst-free pathway provided more than 30 previously (to the best of our knowledge) undescribed chromeno [1,6]naphthyridine derivatives with acceptable yields in PEG-400, which appeared to play a dual role of solvent and catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…However, publications about these are scarce. Among them are ones about rearrangement [ 31 ] and cyclization [ 32 ].…”
Section: Introductionmentioning
confidence: 99%